Pemberian ASI Eksklusif dan Kejadian Diare pada Bayi di Puskesmas Umbulharjo 1 Yogyakarta Tahun 2016 - Ningsih, Ariana Norma; Wahyuningsih, Heni Puji; Margono, Margono (Jurnal Kesehatan Ibu dan Anak, 2017)
Diarrhea disease is the second leading cause of infant morbidity and mortality. High incidence of diarrhea is affected by several factors, one of which is the absence of breastfeeding. The protective effect of breastfeeding is optimal if it is given exclusively. This research aims to identify the correlation between exclusive breastfeeding and incidence of diarrhea in babies at Puskesmas (Public Health Center) Umbulharjo I of Yogyakarta. It belongs an observational analytical research with historical cohort design. The sample size was 84 consisting of 42 mothers with exclusive breastfeeding and 42 without exclusive breastfeeding who had babies aged> 6-12 months from November to December 2016. Data were collected through interviews. Data were analyzed using chisquare, RR, cox regression. The results indicated that the incidence of diarrhea in babies who had a history of receiving exclusive breastfeeding was 11.9% and in infants who did not receive exclusive breastfeeding was 35.7%. The results of the bivariate analysis indicated that the factors related to the incidence of diarrhea were breastfeeding (p-value 0.010, RR 0.333), nutritional status (p-value 0.003, RR 5.0) and occupation (p-value 0.048, RR 2.111). The rate of incidence of diarrhea in babies without exclusive breastfeeding was 27 of 100 babies/ month, which was higher than those with exclusive breastfeeding by 10 of 100 babies/month. The multivariate analysis indicated that in regard to breastfeeding and occupation it was indicated that breastfeeding was the most influential factor in the incidence of diarrhea in babies (Coef B -1.059, p-value 0.046 and RR 0.347). This research concludes that there are correlation between breastfeeding, occupation, nutritional status of infants and the incidence of diarrhea in babies. Breastfeeding is the most influential factor in the incidence of diarrhea in babies. Breastfeeding may lower the incidence of diarrhea in babies.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">